2022
DOI: 10.1039/d2ta04528a
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring defect-type and ligand-vacancies in Zr(iv) frameworks for CO2 photoreduction

Abstract: The nature and degree of defects can fine-tune the light absorption energy (Eabs) and charge transfer energy (ELMCT) of metal-organic frameworks (MOFs), which are important for photocatalytic reactions. Herein, a...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 63 publications
0
26
0
Order By: Relevance
“…In this reaction system, when CO 2 was replaced by N 2 , the CO and CH 4 yields could be negligible, indicating that CO was generated from CO 2 . It can be further proved by the 13 CO 2 isotope tracer experiment and the signal peak at m/z = 45 which belonged to 13 CO 2 . Aer photocatalysis, the MS signal peaks of CO and CH 4 were generated at m/z = 29 and m/z = 17, 37 respectively (Fig.…”
Section: Co 2 Photocatalytic Reduction and Mechanismmentioning
confidence: 74%
See 1 more Smart Citation
“…In this reaction system, when CO 2 was replaced by N 2 , the CO and CH 4 yields could be negligible, indicating that CO was generated from CO 2 . It can be further proved by the 13 CO 2 isotope tracer experiment and the signal peak at m/z = 45 which belonged to 13 CO 2 . Aer photocatalysis, the MS signal peaks of CO and CH 4 were generated at m/z = 29 and m/z = 17, 37 respectively (Fig.…”
Section: Co 2 Photocatalytic Reduction and Mechanismmentioning
confidence: 74%
“…Due to their high Brunauer–Emmett–Teller (BET) specific surface areas ( S BET ), adjustable structure, abundant micropores and unsaturated metal sites, 11 MOFs are widely used for CO 2 capture and photocatalytic reduction. 12 For example, Sun's group 13 synthesized a series of UiO-66–NH 2 with missing-linker/missing cluster defects, and they found that their charge transfer energy and light absorption energy can be fine-tuned, and the CO photocatalytic yield was 21.3 μmol g −1 h −1 . Wang's group constructed a variety of functionalized MOFs and the MOFs showed good photocatalytic CO 2 reduction performance.…”
Section: Introductionmentioning
confidence: 99%
“…6c, once exposed to visible light, OBCP exhibits an enhanced current density response compared with NBCP and SBCP, indicating that OBCP generates more efficient photoexcited charges and significantly accelerates the separation of photogenerated carriers. 46 Furthermore, time-resolved fluorescence decay spectroscopy can characterize the lifetime of the as-prepared samples (Fig. 6d).…”
Section: Resultsmentioning
confidence: 99%
“…Soon after, in a similar report, they further demonstrated that cluster defects are essential for improving MOFs photoactivity, but are not as pronounced as ligand defects. [241] In particular, Gao et al provided more convincing evidence that repair of DE UiO-66 utilizing PSE demonstrates that cluster defects do not enhance photo-nitrogen fixation as significantly as ligand defects. [242] In conclusion, in MOFs photocatalysis, metal centers are more critical redox active sites than organic ligands, which is perhaps the direct reason why cluster defects have been little studied.…”
Section: Cluster Defectsmentioning
confidence: 99%
“…Sun's group modulates the molar ratio of FA and dicarboxylate ligands (ATA) to create a series of Pre UiO-66-NH 2 -ML/MC-X (X = 50, 100, 150, 200) with different defect types (cluster or ligand defects) and degrees of ligand vacancies. [367] Where Pre denotes unactivated by high temperature, X denotes the molar equivalent of FA relative to the ligand, and ML and MC denote the ligand and cluster defects, respectively. The original Zr-UiO-66-NH 2 cell consists of 12 fcu 4[Zr 6 (µ 3 -O) 4 (µ 3 -OH) 4 L 6 ].…”
Section: Defects Engineeringmentioning
confidence: 99%